If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 4 + 5x + 9 = 12x + 4 Reorder the terms: 4 + 9 + 8x + 5x = 12x + 4 Combine like terms: 4 + 9 = 13 13 + 8x + 5x = 12x + 4 Combine like terms: 8x + 5x = 13x 13 + 13x = 12x + 4 Reorder the terms: 13 + 13x = 4 + 12x Solving 13 + 13x = 4 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. 13 + 13x + -12x = 4 + 12x + -12x Combine like terms: 13x + -12x = 1x 13 + 1x = 4 + 12x + -12x Combine like terms: 12x + -12x = 0 13 + 1x = 4 + 0 13 + 1x = 4 Add '-13' to each side of the equation. 13 + -13 + 1x = 4 + -13 Combine like terms: 13 + -13 = 0 0 + 1x = 4 + -13 1x = 4 + -13 Combine like terms: 4 + -13 = -9 1x = -9 Divide each side by '1'. x = -9 Simplifying x = -9
| 11+[8+(-4)]= | | 5a+4b=-28 | | 81w^2-100p^2= | | 3*-1+4= | | (7x+5y)+(-8x-9y)= | | 9y^4(4y^2-8y+6)= | | -13x=221 | | y^2-17y+72=0 | | y^2-15y+56=0 | | -3(z-4)= | | -3z-2z= | | x-7.9=-5.5 | | 9x-5=76 | | 8x+24=48 | | 6x+12=60 | | 0=-8y+21 | | -2x^2+6x+9=0 | | a^4b+a^2b^3= | | 0.05x-0.6=5.3 | | 12=2x+2x+2x | | 14=2x+2y+4z | | w=m-5L | | 2-6x=7x+2 | | 20g^2=16g | | 8+3(4x-4)=5-4(2x+1) | | X=6+-1y+-1z | | -24c^2=36 | | 3x-y=-3 | | (x+2)(x-1)=40 | | 3m=2 | | 6d=0 | | 3x+12=7x-16 |